Chapter Of the spaces between: prepositional events throughout the Festival de Marseille - Kimmel, Anna Jayne (Ricerche. Architettura, Pianificazione, Paesaggio, Design, 2022)
This chapter considers the Festival de Marseille-danse et arts multiple 2017 as a successful apparatus of transition from positions of non-place to place in one of Europe's most diverse cities. Through its temporary installation, the festival crossed spatial, aesthetic, and thematic divisions of the center and periphery, constructing bridges of movement between these invisible borders. In doing so, this chapter troubles the traditional affirmation that the value of performance is most prominently interpreted during its enactment. Instead, it leverages the spatial turn of French theory to emphasize that the festival's significance extends to the process of coming-to-stage, and highlights participant interactions with the city as facilitated by the festival's infrastructure. In re-framing the boundaries of the festival's intended performance scene from the aestheticized proscenium to the larger social context of Marseille, a voyeuristic and objectifying gaze is removed from the staged bodies and redirected to a new embodied praxis of inclusion and exclusion, rehearsed for, and by, the performer whose ephemeral offering is too often pushed to the periphery or essentialized at the center but never allowed full placement. To move away from accentuating the fixed nouns and verbs of place in a recapitulation of the actors and how they danced, this chapter instead looks toward the mechanisms that scaffolded the relationship between the two-the grammar of the event-which both exceeded and preceded its actual content. What emerges is an attention toward prepositional events, the mechanics of societies that facilitate and articulate such relations.